2011
DOI: 10.1103/physreve.84.020301
|View full text |Cite
|
Sign up to set email alerts
|

Elastic weakening of a dense granular pack by acoustic fluidization: Slipping, compaction, and aging

Abstract: Sound velocity measurements in dense glass bead packs reveal significant softening effect at large amplitudes, due to the frictional nonlinearity at the grain contacts. Beyond a certain amplitude, the sound-matter interaction becomes irreversible, leaving the medium in a weakened and slightly compacted state. A slow recovery of the initial elastic modulus is observed after acoustic perturbation, revealing the plastic creep growth of microcontacts. The cross-correlation function of configuration-specific acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 25 publications
8
114
3
Order By: Relevance
“…Furthermore, we showed that an amplitude threshold exists for triggering of frictional weakening events and this threshold is larger for higher confining stresses. This is also in agreement with the recent experimental observation by Jia et al where they found that the acoustic fluidization threshold increases by increasing the confining pressure of the granular medium [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we showed that an amplitude threshold exists for triggering of frictional weakening events and this threshold is larger for higher confining stresses. This is also in agreement with the recent experimental observation by Jia et al where they found that the acoustic fluidization threshold increases by increasing the confining pressure of the granular medium [11].…”
Section: Discussionsupporting
confidence: 93%
“…The intrinsic stick-slip dynamics of a granular layer can be perturbed by external factors including boundary vibrations. Laboratory scale observations as well as Discrete Element Method (DEM) simulations show and confirm that mechanical and acoustic vibrations with adequate amplitudes can change the mechanical and frictional properties of a confined and sheared granular layer, and consequently its macro-scale response [6,7,8,9,10,11,12]. Many aspects of this vibration-induced changes including its grain-scale mechanisms, its dependence on the loading state of the granular layer and on the vibration amplitude are unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The method showed convincing results for the study of linear and nonlinear scattering regimes in granular media. 8,9 As shown in Fig. 1(c), three parameters are extracted from the CCM: (i) the intercorrelation amplitude for a 0-shift, (ii) the time-shift value s max corresponding to the maximum intercorrelation, and (iii) the value of this maximum.…”
mentioning
confidence: 99%
“…This behaviour arises from rearrangements of the contact network, resulting in a reduction in the average contact number but without significant rearrangement of particle positions [28]. However, the effect of friction on the elastic softening [9,30] is absent in these frictionless systems.…”
Section: /2mentioning
confidence: 99%
“…A granular solid shows strong nonlinear elasticity and sound propagation provides a footprint of this feature [2][3][4][5]. The nonlinear dynamic response found in granular media such as resonance frequency softening, slow dynamics and harmonic generation [6][7][8][9] is very similar to those discovered in rocks [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%